The use of Hardy–Weinberg Equilibrium in clonal plant systems. Issue 4 (25th January 2016) - Douhovnikoff, Vladimir; Leventhal, Matthew
Abstract: Traditionally population genetics precludes the use of the same genetic individual more than once in Hardy–Weinberg (HW) based calculations due to the model's explicit assumptions. However, when applied to clonal plant populations this can be difficult to do, and in some circumstances, it may be ecologically informative to use the ramet as the data unit. In fact, ecologists have varied the definition of the individual from a strict adherence to a single data point per genotype to a more inclusive approach of one data point per ramet. With the advent of molecular tools, the list of facultatively clonal plants and the recognition of their ecological relevance grows. There is an important risk of misinterpretation when HW calculations are applied to a clonal plant not recognized as clonal, as well as when the definition of the individual for those calculations is not clearly stated in a known clonal species. Focusing on heterozygosity values, we investigate cases that demonstrate the extreme range of potential modeling outcomes and describe the different contexts where a particular definition could better meet ecological modeling goals. We emphasize that the HW model can be ecologically relevant when applied to clonal plants, but caution is necessary in how it is used, reported, and interpreted. We propose that in known clonal plants, both genotype (GHet) and ramet (RHet) based calculations are reported to define the full range of potential values and better facilitate cross‐study comparisons. Abstract : There is an important risk of misinterpretation when HW calculations are applied to a clonal plant not recognized as clonal, as well as when the definition of the individual for those calculations is not clearly stated in a known clonal species. Focusing on heterozygosity values we investigate cases that demonstrate the extreme range of potential modeling outcomes and describe the different contexts where a particular definition could better meet ecological modeling goals. We emphasize that the HW model can be ecologically relevant when applied to clonal plants, but caution is necessary in how it is used, reported and interpreted.